Georgia : Public Expenditure Review - World Bank (Washington, DC, 2013)
Like other low-income countries, Georgia's ability to reduce poverty and meet the Millennium Development Goals (MDGs) by 2015 will depend crucially on its ability to sustain per-capita GDP growth and to use effectively and efficiently its scarce public resources. Indeed, increased public expenditures will not result in improved social outcomes unless current productivity levels are improved. This report shows that weaknesses in Georgia's public expenditure management systems have led to serious inefficiencies and inequities in the use of public resources and have prevented the necessary restructuring in public expenditures. The first three chapters explore sources of these systemic problems in the context of macroeconomic management, revenue policy and administration, and budget management systems. Subsequent chapters explore the scope for strengthening budget management systems in the areas most critical for poverty reduction and the attainment of MDGs: local governments and social sector spending. These chapters both corroborate and supplement with further detail the core constraints on public expenditure restructuring seen in the earlier chapters, but also map out the complementary components of a reform strategy which recognizes the need for parallel action by central agencies, line ministries, and local governments. Given that identified weaknesses cannot all be addressed at once, the PER offers an approach to sequence expenditure management reforms in phases.